Numerical study of pressure drops and flow characteristic in high temperature air-water stratified flow using the AIAD model - Eli Kumolosari; Bahrul Jalaali (Institut Teknologi Dirgantara Adisutjipto, 2022)
In geothermal power plant systems, two-phase flow measurement is very important for the management and control of different processes. Two of the important parameters in two-phase flow are the flow regime (flow pattern) and pressure drop. In this study, high temperature air-water pressure drop and flow regime were investigated numerically, as a basic study of two-phase phenomena in geothermal power plant, using AIAD model. The vapor and water superficial velocities were ranged at 3.9 – 6.6 m/s and 0.013-0.022 m/s, respectively. The computational domain was adjusted on a horizontal pipe with 255mm in diameter and 8000mm in length while the temperature and inlet pressure condition were set to 433K and 6bar. The simulation results showed a good agreement on predicting flow regime compared with the flow regimes that obtained experimentally by previous work whereby stratified and wavy flow were clearly observed. The results are beneficial to enhance the understanding of flow characteristics regarding geothermal wells and their potential power which is important to the investigation on geothermal industry